Clear Lens Phacoemulsification Untuk Koreksi Miopia Tinggi - Syauqie, Muhammad (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: High myopia correction with clear lens extraction, with or without IOL implantation, remains controversial and associated with a high risk of postoperative complications, especially retinal detachment. However, advanced technology development in the cataract surgery field had resulted in excellent surgical outcomes with a very low complication rate. In this article, we will present an outcome of clear lens phacoemulsification for high myopia correction in four eyes from two patients.Case presentation: Two women with high myopia undergone clear lens phacoemulsification with supracapsular tilt and tumble technique. IOL calculation using SRK-T formula. Both patients had 20/20 postoperative visual acuity in both eyes, which remains until one year postoperative. No retinal abnormalities found in both patients.Conclusion: Clear lens phacoemulsification for high myopia correction is an effective procedure and can prove excellent visual outcome for a long-term period. It can be considered as an alternative method for high myopia management.